Integration of the National Sports Grand Design Strategy (DBON) in Organizing Sports Events: Case Study of PON XXI ACEH-SUMUT 2024 - Adi Rahadian; Andi Kurniawan Pratama; Asep Ramdan Afriyuandi; Muhamad Guntur Gaos Sungkawa; Adriyan Adriyan; Ariel Erlangga; Lutfi Nur; Oman Hadiana; Rabwan Satriawan; Vicki Ahmad Karisman; Putu Citra Permana Dewi; Kadek Dian Vanagosi; Komang Ayu Krisna Dewi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
In every sporting event there is always an event identity that is able to represent the image of the region and country in its implementation. The purpose of this study is to explore the case study of PON XXI 2024 within the framework of achievement development. The method used in this study is a qualitative method. Participants in the study consisted of elite athletes (PON Program), coaches, officials, and sports policy academics with a total of 12 participants. Data collection techniques used in this study were observation, interviews, document studies. Data analysis techniques used in this study include data reduction analysis, data presentation, drawing conclusions assisted by the Nvivo application. The results of this study, the integration of DBON strategies starting from talent identification, athlete career advancement, and multi-level competition opportunities. In the context of DBON development, the role of the central government, regions, and KONI cannot be ignored. The unity of stakeholders functions as the main manager who coordinates and integrates all aspects of DBON, both at the central and regional levels